Determination of Polycyclic Aromatic Hydrocarbons (PAHs) and their Sources in Ganga River Water, Uttar Pradesh, India - Sonwani, Poonam; Singh, Chetan (Asian Journal of Biological and Life Sciences)
Aims: To evaluate the US EPA listed sixteen carcinogenic and mutagenic Polycyclic aromatic hydrocarbons (PAHs) contamination in Ganga River water which supports the livelihood of more than 400 million people in many ways such as drinking, bathing, industrial, agricultural, ritualistic and other household activities. Materials and Methods: The Ganga River water was collected from three cities namely Jajmau (Kanpur), Katari Bhalepur (Fatehpur) and Kursinda Kachar. Sample preparation was carried out following APHA AWWA 610 method and analyzed by High Performance Liquid Chromatography (HPLC) equipped with a UV detector. Results: In the present study, eight PAHs with their mean concentration were as Acy (4.897±5.3709) > Ace (0.7081±0.8232) > Fln (0.6239±0.3327) > Phe (0.2443±0.226) > Flu (0.1555±0.0737) > Chy (0.0232±0.0082) > Ant (0.01166±0.00324) > BaA (0.0096±0.0046) in Jajmau (Kanpur) while eleven PAHs were orderly as Acy (0.9456±0.2108) > Ace (0.3775±0.0546) > Phe (0.1503±0.0997) > Flu (0.1202±0.0170) > BaA (0.0815±0.0096) > BahA (0.0559±0.0014) > Chy (0.0557±0.039) > Fln (0.0446±0.0096) > BbF (0.0221±0.0075) > BkF (0.012±0.0022) > BaP (0.0098±0.00176 in Katari Bhalepur (Fatehpur). At Kaushambi Acy (0.4135±0.1575) > Ace (0.2177±0.0864) > Flu (0.15873±0.0456) > Fln (0.1136±0.1008) > BahA (0.099±0.0587) > BghiP (0.0916±0.0496) > BkF (0.0787±0.0449) > Phe (0.0747±0.01310) > IP (0.0467±0.0162) > BaA (0.0368±0.0284) > Chy (0.0333±0.0204) > BaP (0.0283±0.01723) > BbF (0.028±0.0120) > Ant (0.0027±0.00015) was detected. Conclusion: It was determined that Ganga River water at all study stations was contaminated by PAHs. The total PAHs measured in Ganga River water at all three cities were above the recommended safe limits, and also noticed that Ganga River water is contaminated by LMW PAHs at Kanpur while Fatehpur and Kaushambi were contaminated by both LMW and HMW PAHs which are more toxic over LMW PAHs.
Keywords: Ganga River; HPLC; PAHs; UV detector